The relationship between anxiety and COVID‐19‐associated isolation and lifestyle changes in the university community as a result of the SARS‐CoV‐2 pandemic - Felipe Saceanu Leser; Mirella Araújo Ribeiro; Lucas Dalsente Romano da Silva; Renato Garcia Domingues; Tiago Fleming Outeiro; Kevin Boyé; Eduardo Coelho Cerqueira; Fabiano Lacerda Carvalho; Phelippe doCarmo Gonçalves (Mental Health Science, 2024)
Abstract In 2020, the novel severe acute respiratory syndrome coronavirus outbreak emerged as a public health emergency. Three years later, we are still assessing the effects caused by the coronavirus disease (COVID‐19) and by the lifestyle changes due to prevention measures, like social isolation. Here, we assessed the profile of both the anxiety screening scores and anthropometric variables in the university community, associated with the isolation due to the COVID‐19 pandemic. We analyzed social and epidemiological associated factors for anxiety and weight change to address and better identify the physical and mental conditions aggravated during the pandemic. This is a cross‐sectional study based on the 7‐item Generalized Anxiety Disorder Scale questionnaire applied virtually to university students and professors in the State of Rio de Janeiro (n = 480). In our population cohort, we showed that the majority of individuals showed moderate to severe anxiety and increased body weight during the COVID‐19 pandemic. The major demographic associated factors for higher anxiety levels were young age, female gender, and low family income. The main modifiable associated factors for both anxiety and weight gain were the negative changes in living habits. In addition, there was a trend toward severe anxiety and greater weight change in people with increased time in social isolation. In view of these results, we suggest that bad habits, adopted during the COVID‐19 pandemic, were the main reason for the high anxiety levels found in the studied population.